2021
DOI: 10.21660/2021.88.gxi255
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Flexural Behavior of Corroded Rc Beams Strengthened by CFRP Sheets

Abstract: In the present study, a series of numerical modeling is performed in order to investigate the structural behavior of corroded reinforced concrete beams externally strengthened to tension area with CFRP (Carbon Fiber Reinforced Polymer) with the aid of the finite element method adopted. A three-dimensional model employing the nonlinear characteristics of materials (e.g. elasto-plastic material model of steel reinforcement and damaged concrete model due to corrosion, bond stress-slip behavior between steel and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Gotame et al [5] studied FRP-strengthened 2 of 15 corroded RC beams through nonlinear finite element analysis, and the results showed that the interface properties between FRP and concrete were crucial for accurately predicting the bearing capacity and failure modes of the strengthened beams. Tran et al [6] numerically modeled CFRP-strengthened corroded RC beams using the finite element method to predict the flexural load capacity of the strengthened beams, and the results showed that the predicted residual load capacity was in good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 93%
“…Gotame et al [5] studied FRP-strengthened 2 of 15 corroded RC beams through nonlinear finite element analysis, and the results showed that the interface properties between FRP and concrete were crucial for accurately predicting the bearing capacity and failure modes of the strengthened beams. Tran et al [6] numerically modeled CFRP-strengthened corroded RC beams using the finite element method to predict the flexural load capacity of the strengthened beams, and the results showed that the predicted residual load capacity was in good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 93%